SWOT Analysis of Dabbawalla’s - Sawant, Sarika (Prabandhan: Indian Journal of Management, 2010)
Dabbawallas (Tiffin carriers) pick up the lunch boxes in the morning and deliver it on time to the place of work everywhere in Mumbai and delivers it back to the residence at a very economical price. There are about 4500 dabbawallas across Mumbai who coordinate with each other for picking up and delivering the Tiffin over 1, 75, 000 Mumbaikers everyday in a 3 hour period through 60 kms of public transport. The organization is really a marvel because it achieves a high level of efficiency and performance without any documentation, without computers and without an educational work force. Yet, they are the ultimate practitioners of logistic management. The present article examines Dabbawallas’ organisation from SWOT point of view to know strength that is inherent in their system and weaknesses arising out of conventional technology. There are several opportunities for them, but they are bound by certain threats to survive.